Introduction to the Special Issue on Microwaves in Climate Change - Peter H. Siegel (IEEE Journal of Microwaves, 2024)
IEEE Journal of Microwaves is extremely pleased to host this special topic, which was inspired by our editorial series article, “Making Waves: Microwaves in Climate Change,” released in July 2023. The papers included in this special issue cover a wide swath of topics that involve microwave techniques and instrumentation applied to problems related to climate change. These include energy use and distribution, atmospheric chemistry, meteorology, water resource management, pollution monitoring, power transfer, heating, energy reuse and efficiency, waste management and animal migration tracking. We hope that this special issue will bring additional scientists into the microwave publishing community and inspire more microwave engineers to seek out geophysicists, Earth scientists, environmentalists, climatologists, geochemical engineers, energy and power specialists, resource managers, and other technical experts who might benefit from the instrumentation, knowledge, and skillsets within our community.